Rupert Murdoch: integrating media and political power - Williams, Granville (Henry Stewart Talks, 2017)
The case study examines the large media empire owned by Rupert Murdoch in the UK and how his diverse holdings influence both economics and politics in the country. It asks whether Murdoch’s influence has enabled a distortion of government policy in communications as well as in other issues.